National Youth development in the Bahamas : a model for the Caribbean - Fraser, A. Gabriella (CSIS Americs Program WashingtonUS, 1997)
Focuses on the plight of Bahamian youth. Looks at existing programmes administered through the Ministry of Youth, Sports and Culture. Presents a plan for national youth development.